1933 Wyo. Sess. Laws 117, ch. 101, §§ 1-4. - (:unkn) unknown (General Publisher, 1933)
All wholesalers, retailers, dealers and pawn brokers are hereby required to keep a record of all firearms which may come into their possession, whether new or second hand, which record shall be known as the Firearms Register. Such register shall contain the following information, to wit: the name of the manufacturer, person, persons, firm or corporation from whom the firearm was obtained, the date of its acquisition, its manufacturer’s number, its color, its caliber, whether the same is new or second hand, whether it is automatic, a revolver, a single shot pistol, a rifle, a shot gun or a machine gun, the name of the party to whom said firearm is sold in such purchasers handwriting and the date of such sale
--
Keywords: REGISTRATION